STM tip-assisted engineering of molecular nanostructures: PTCDA islands on Ge(001):H surfaces - Ahmad Zebari, Amir A.; Kolmer, Marek; Prauzner-Bechcicki, Jakub S. (Beilstein Journal of Nanotechnology, 2013)
Islands composed of perylene-3,4,9,10-tetracarboxylic dianhydride (PTCDA) molecules are grown on a hydrogen passivated Ge(001):H surface. The islands are studied with room temperature scanning tunneling microscopy and spectroscopy. The spontaneous and tip-induced formation of the top-most layer of the island is presented. Assistance of the scanning probe seems to be one of the factors that facilitate and speed the process of formation of the top-most layer.
Keywords: molecular nanostructures; scanning tunneling microscopy; tip-induced processes

(untitled) - Otero, R.; Gallego, J. M.; Vázquez de Parga, A. L.; Martin, N.; Miranda, R. (Adv. Mater., 2011)

(untitled) - Palma, C.-A.; Cecchini, M.; Samori, P. (Chem. Soc. Rev., 2012)

(untitled) - Tait, S. L. (ACS Nano, 2008)

(untitled) - Prauzner-Bechcicki, J. S.; Godlewski, S.; Szymonski, M. (Phys. Status Solidi A, 2012)

(untitled) - Gross, L.; Moll, N.; Mohn, F.; Curioni, A.; Meyer, G.; Hanke, F.; Persson, M. (Phys. Rev. Lett., 2011)

(untitled) - Repp, J.; Meyer, G.; Stojković, S. M.; Gourdon, A.; Joachim, C. (Phys. Rev. Lett., 2005)

(untitled) - Liljeroth, P.; Repp, J.; Meyer, G. (Science, 2007)

(untitled) - Abel, M.; Clair, S.; Ourdjini, O.; Mossoyan, M.; Porte, L. (J. Am. Chem. Soc., 2011)

(untitled) - Wang, Y.; Kröger, J.; Berndt, R.; Tang, H. (J. Am. Chem. Soc., 2010)

(untitled) - Bombis, C.; Kalashnyk, N.; Xu, W.; Lægsgaard, E.; Besenbacher, F.; Linderoth, T. R. (Small, 2009)

(untitled) - Rossel, F.; Pivetta, M.; Patthey, F.; Ćavar, E.; Seitsonen, A. P.; Schneider, W.-D. (Phys. Rev. B, 2011)

(untitled) - Bombis, C.; Ample, F.; Lafferentz, L.; Yu, H.; Hecht, S.; Joachim, C.; Grill, L. (Angew. Chem., Int. Ed., 2009)

(untitled) - Ramoino, L.; von Arx, M.; Schintke, S.; Baratoff, A.; Güntherodt, H. J.; Jung, T. A. (Chem. Phys. Lett., 2006)

(untitled) - Such, B.; Goryl, G.; Godlewski, S.; Kolodziej, J. J.; Szymonski, M. (Nanotechnology, 2008)

(untitled) - Godlewski, S.; Goryl, G.; Kolodziej, J. J.; Szymonski, M. (Appl. Surf. Sci., 2010)

(untitled) - Mayne, A. J.; Riedel, D.; Comtet, G.; Dujardin, G. (Prog. Surf. Sci., 2006)

(untitled) - Bellec, A.; Ample, F.; Riedel, D.; Dujardin, G.; Joachim, C. (Nano Lett., 2009)

(untitled) - Gruyters, M.; Pingel, T.; Gopakumar, T. G.; Néel, N.; Schütt, C.; Köhler, F.; Herges, R.; Berndt, R. (J. Phys. Chem. C, 2012)

(untitled) - Godlewski, S.; Kolmer, M.; Kawai, H.; Such, B.; Zuzak, R.; Saeys, M.; de Mendoza, P.; Echavarren, A. M.; Joachim, C.; Szymonski, M. (ACS Nano, 2013)

(untitled) - Vaurette, F.; Nys, J. P.; Grandidier, B.; Priester, C.; Stievenard, D. (Phys. Rev. B, 2007)

(untitled) - Ogawa, T.; Kuwamoto, K.; Isoda, S.; Kobayashi, T.; Karl, N. (Acta Crystallogr., Sect. B, 1999)

(untitled) - Forrest, S. R. (Chem. Rev., 1997)

(untitled) - Radny, M. W.; Shah, G. A.; Schofield, S. R.; Smith, P. V.; Curson, N. J. (Phys. Rev. Lett., 2008)

(untitled) - Nakatsuji, K.; Takagi, Y.; Komori, F.; Kusuhara, H.; Ishii, A. (Phys. Rev. B, 2005)

(untitled) - Kolmer, M.; Godlewski, S.; Kawai, H.; Such, B.; Krok, F.; Saeys, M.; Joachim, C.; Szymonski, M. (Phys. Rev. B, 2012)

(untitled) - Tautz, F. S. (Prog. Surf. Sci., 2007)

(untitled) - Hill, I. G.; Kahn, A.; Soos, Z. G.; Pascal, R. A., Jr (Chem. Phys. Lett., 2000)

(untitled) - Tsiper, E. V.; Soos, Z. G.; Gao, W.; Kahn, A. (Chem. Phys. Lett., 2002)

(untitled) - Zahn, D. R. T.; Gavrila, G. N.; Gorgoi, M. (Chem. Phys., 2006)

(untitled) - Yim, S.; Kim, K.-i.; Jones, T. S. (J. Phys. Chem. C, 2007)

(untitled) - Zhong, D. Y.; Hirtz, M.; Wang, W. C.; Dou, R. F.; Chi, L. F.; Fuchs, H. (Phys. Rev. B, 2008)